Astatine-211 based radionuclide therapy: Current clinical trial landscape - Albertsson, Per; Bäck, Tom; Bergmark, Karin; Hallqvist, Andreas; Johansson, Mia; Aneheim, Emma; Lindegren, Sture; Timperanza, Chiara; Smerud, Knut; Palm, Stig (Frontiers in Medicine, 2023)
Astatine-211 (211At) has physical properties that make it one of the top candidates for use as a radiation source for alpha particle-based radionuclide therapy, also referred as targeted alpha therapy (TAT). Here, we summarize the main results of the completed clinical trials, further describe ongoing trials, and discuss future prospects.